Modifying Drucker-Prager Criterion for Elastoplastic Porous Rocks Using a Numerical Integration Algorithm - Manouchehr Sanei (Ravishʹhā-yi taḥlīlī va ʻadadī dar muhandisī-i maʻdin (Journal of analytical and numerical methods in mining engineering), 2024)
In the topics related to rock mechanics and geotechnics, elastoplastic criteria are of special importance. This importance makes their numerical implementation necessary. Although most of the existing software in the field of rock mechanics and geotechnics have elastoplastic criteria, the lack of access to their coding core makes it practically impossible for researchers to develop them. Therefore, considering the importance of elastoplastic criteria and the complexity of their implementation, in this study, a suitable scheme was presented to improve the elastoplastic numerical integration algorithm of Darker-Prager criteria. The developed algorithm includes two steps of elastic trial and plastic return-mapping algorithm. In the proposed model, if the elastic trial step is in the elastic domain or on the yield surface, the answer of elasticity is approved. Otherwise, if the trial stress can not confirm the desired conditions in the first step, it is executed by the plastic return-mapping algorithm. This process has been done comprehensively and separately for Drucker-Prager's cone and apex to be able to express the elastoplastic behavior of the material optimally. The presented model was analyzed for the porous rock sample and its validation was confirmed by comparing the numerical results with the laboratory data.